Immune responses to Streptococcus sobrinus surface protein antigen A expressed by recombinant Salmonella typhimurium. - Doggett, T A (1993)
In this study, we used a vaccine strain of Salmonella typhimurium to express antigenic determinants of the SpaA antigen of Streptococcus sobrinus, which is involved in the caries-forming process. We cloned either a single repeat (pYA2901) or three tandem repeats (pYA2905) of the 0.48-kb fragment of the spaA gene, which codes for an important component of the SpaA protein, plus a 1.2-kb minor antigenic determinant and measured the resulting immune responses to SpaA in orally immunized BALB/c mice. The single or triple repeat of the spaA gene fragment was inserted into the Asd+ vector pYA292 and was transformed into the S. typhimurium delta cya delta crp vaccine strain chi 4072 containing delta asd in the chromosome. Female BALB/c mice were then orally immunized with two doses of the S. typhimurium containing either of the two SpaA constructs, and the immune responses to the expressed SpaA protein were assessed. Significant serum immunoglobulin G (IgG) anti-SpaA titers were detected in mice immunized with chi 4072(pYA2905) but not chi 4072(pYA2901). Salivary anti-SpaA IgA titers were minimal and were only detected in mice immunized with S. typhimurium expressing the SpaA encoded by pYA2905. Intestinal anti-SpaA IgA titers, however, were detected in both groups of mice, particularly in mice immunized with chi 4072(pYA2905). An oral booster 26 weeks after the initial series of immunizations resulted in increased serum IgG titers in both chi 4072(pYA2901)- and chi 4072(pYA2905)-immunized animals, particularly in the chi 4072(pYA2905)-immunized animals. No anamnestic IgA response was detected in the saliva following the booster immunization.